Clinical observation of autologous platelet rich fibrin assisted revascularization of mature permanent teeth - Zhaojun Wu; Yao Lin; Xuehong Xu; Zhiqun Chen; Yan Xiang; Lvli Yang; Wei Zhang; Suli Xiao; Xiaoling Chen (Head & Face Medicine, 2023)
Abstract Objective To investigate the clinical observation of autologous platelet-rich fibrin (PRF) assisting the revascularization of mature permanent teeth. Methods Twenty patients with mature permanent teeth were divided into experimental group and control group. The control group was treated with classic revascularization, and the experimental group was treated with PRF-assisted mature permanent tooth revascularization. Results After treatment, the total effective rate of the experimental group (100.00%) was higher than that of the control group (50.00%); the thickness of the root canal wall of the experimental group was higher than that of the control group, and the crown root length was lower than that of the control group; The bite degree, chewing function, color, overall aesthetic score, and satisfaction rate of the patients were higher, and the difference was statistically significant (P < 0.05). Conclusion Autologous PRF assists in revascularization of mature permanent teeth, which can achieve ideal results, and promote pulp regeneration.